2021
DOI: 10.4012/dmj.2020-341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver diamine fluoride preparations on biofilm formation of <i>Streptococcus mutans </i>

Abstract: Effects of silver diamine fluoride preparations (SDFs) on cariogenic biofilm formation on root dentin (RD) were investigated. Streptococcus mutans (S. mutans) biofilms were formed on bovine RD blocks coated with one of three the SDFs (38%-SDF, 3.8%-SDF and 35%-SDF+potassium-iodide; SDF+KI) and a non-coated Control which were quantified (spectrometric-measurement) and thickness measured (optical coherence tomography) after 20 h. Bacterial viability test (BacLight) and biofilm-morphometry (SEM) of 2 h biofilms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…It is also suggested that the application of the KI solution might reduce the number of silver ions [29]. In contrast to this, the use of lower concentration SDF than in previous study [28,29] and multispecies bacteria might contributed to the result of this study. Biofilms comprising multiple bacterial species are more resistant to antibacterial treatment than when comprising a single species because of their thickness, complexity of structure, and interactions between bacteria [30].…”
Section: ⅳ Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is also suggested that the application of the KI solution might reduce the number of silver ions [29]. In contrast to this, the use of lower concentration SDF than in previous study [28,29] and multispecies bacteria might contributed to the result of this study. Biofilms comprising multiple bacterial species are more resistant to antibacterial treatment than when comprising a single species because of their thickness, complexity of structure, and interactions between bacteria [30].…”
Section: ⅳ Discussionmentioning
confidence: 53%
“…The inhibition ability of the biofilm formation in the SDFKI group was smaller than that in the SDF group, but there was no statistically significant difference. Takahashi et al [28] reported that when SDFKI was applied, the formation of S. mutans bacterial films significantly increased because silver particles might be washed more easier compared to the application of 38% SDF. It is also suggested that the application of the KI solution might reduce the number of silver ions [29].…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…In 2015, Savas et al reported that SDF inhibited the growth of the S. mutans biofilm [ 57 ]. Other studies revealed similar results for the strong antibacterial effect of SDF in inhibiting the growth of bacterial biofilm with regard to the mono-species of S. mutans or Actinomyces naeslundii [ 56 , 58 , 59 ], the dual-species of S. mutans and Lactobacillus acidophilus [ 42 ], and even a multi-species biofilm composed of S. mutans , Streptococcus sobrinus , L. acidophilus , Lactobacillus rhamnosus , and A. naeslundii [ 60 ].…”
Section: Sdf’s Effectiveness Against Carious Lesionsmentioning
confidence: 71%
“…El Fluoruro Diamino de Plata, es una solución que contiene Plata Iónica, Fluoruro y Amoníaco que detiene el progreso de las lesiones cariosas y previene el desarrollo de caries en el futuro, 18,19 la partícula de Plata se extiende hacia los túbulos de dentina y proporciona la actividad antimicrobiana de amplio espectro del material, ya que afecta la permeabilidad de la membrana celular impidiendo el intercambio de sustancias del interior de la bacteria hacia el medio, a su vez afecta el metabolismo impidiendo que obtenga energía para sobrevivir y afecta el funcionamiento del ADN, lo que impide la replicación del microorganismo, además inhibe la formación de biopelícula; 1,20,21,22 sin embargo, podría crear algunos problemas de unión en la adhesión de las restauraciones de resina compuesta aunque se considera que la evidencia al respecto es insuficiente, 16,23 además de pigmentaciones en caso de que la pared de estructura sana sea muy delgada; 1,3,12,16,23,24,25 por otra parte, el Fluoruro penetra más profundamente en el diente gracias al Diamino de Plata en comparación con otras soluciones de Fluoruro, facilitando el depósito de Fluoruro en la estructura del diente 26,27 y en consecuencia el componente de Fluoruro contribuye a la remineralización y formación de Fluoropatita produciendo estructuras dentales más duras y resistentes a las caries, debido a la reacción química del Ag (NH3)2F en contacto con la pieza dental. 17,24,28,29 Indicaciones de uso:…”
Section: Desarrollo De La Revisión Narrativa Fluoruro Diamino De Plata Más Yoduro De Potasio (Sdf+ki)unclassified
“…25,39 El seguimiento de grandes lesiones o lesiones en áreas difíciles de limpiar se puede combinar con el uso de restauraciones de ionómero de vidrio o tratamiento restaurador tradicional, según las circunstancias del paciente. 9,22,40 En cuanto a su uso se recomienda:…”
Section: Desarrollo De La Revisión Narrativa Fluoruro Diamino De Plata Más Yoduro De Potasio (Sdf+ki)unclassified